KAJIAN PELAKSANAAN SERTIFIKASI GURU DALAM JABATAN - F, Totok Sumryanto (Jurnal Penelitian Pendidikan, 2010)
The purpose of the research is to discover and develop: (1) the effectiveness of the components of a portfolio documents in the development of the teaching profession, (2) the mechanism of recruitment of assessors and instructors for teacher certification, (3) the proposed mechanism of the teacher as a participant in the teacher certification, and (4) implementation of teaching profession training. This research was carried out with the eklektik approach to use or modify the educational research & development, which according to borg & gall (1983: 775-776) is divided into 7 stages. Components of teaching profession development, which is seen to have great impact, are: (1) lesson plan and implementation (2) academic achievement, (3) academic qualifications, (4) the work of professional development, (5) awards in the field of education, (6) education and training, and (7) participation in scientific forums. The assessment component of the supervisor and the experience in education and social organization are considered not supporting teaching profession development. Keywords: teacher certification, implementation, effectiveness